Study on Beam-Column Joints with Self Compacting Concrete (International Journal of Innovative Research in Engineering & Management, 2022)
Innovative concrete known as Self Consolidating Concrete (SCC) does not require vibration  for placement or compaction. Even in the midst of  crowded reinforcement, it can flow under its own weight,  completely filling forms and attaining full compaction.  Self- Consolidating Concrete has unique characteristics  from regular concrete. The workability characteristics of  self-consolidating concrete containing fly ash and silica  fume with super plasticizer as the silica fume are  examined in this research. Workability tests including the  slump flow, V-funnel, and L-Box tests are used to assess  the workability properties of SCC such as filling ability,  passing ability, and segregation resistance. The cubes'  compressive strength at 7 and 28 days was also measured,  and it was discovered that the mixture had an excellent  compressive strength.
Keywords: Concrete; compressive strength; flexural strength; tensile strength; fine aggregate; quarry dust; silica fume